Experimental and numerical study on performance enhancement of photovoltaic panel by controlling temperature with phase change material. (13th May 2021) - Li, Wei; Guan, Yaru; Zhang, Xu; Zhao, Jun
Summary: In order to enhance the electricity generation performance of photovoltaic (PV) panel, experimental and numerical studies were carried out to control the temperature by using phase change material (PCM). The PV combined with PCM (PV‐PCM) device and PV‐PCM with foam copper were designed, and their temperature, voltage, and output power were measured and compared with those of PV panel. The mathematical model of heat transfer for PV‐PCM was established and verified by experiment. And the influences of PV‐PCM tilt angle, PCM properties and thickness, and ambient temperature on the temperature control effect were studied numerically. The results illuminate that the PV panel's temperature decreases significantly with the using of PCM, which correspondingly enlarges its open circuit voltage and output power. And the PCM with foam copper has a better effect. The temperature control effect of the PV‐PCM system is better with the increase of the tilt angle, the PCM thermal conductivity and thickness, and the decrease of PCM phase change temperature. But there are limited conditions for them. The higher the ambient temperature, the worse the temperature control effect. The present study has important reference value for PV performance enhancement. Abstract : PCM, especially with foam copper, can significantly control the PV panel temperature and improve its performance. A greater inclination angle leads to a lower temperature of PV‐PCM. PCM with low melting temperature and high thermal conductivity makes low temperature of PV panel. The increase of PCM thickness leads to the decrease of PV panel temperature and high material cost. High PV temperature caused by ambient temperature rising can be mitigated by adopting higher melting temperature PCM, etc.